(2) تحديد توجهات تعميق التصنيع المحلي في مصر في ضوء الدروس المستفادة من جائحة كورونا Defining trends for deepening Egypt's industrialization in the light of lessons learned from the Corona virus - أ.د. سهير أبو العينين (معهد التخطيط القومي, 2026)
أكدت جائحة كورونا أهمية تحقيق قدر معقول من الاكتفاء الذاتي من السلع الاستراتيجية لزيادة قدرة الدولة على مواجهة الأزمات. وتهدف هذه الدراسة إلى تحديد توجهات تعميق التصنيع المحلي في مصر في ضوء الدروس المستفادة من جائحة كورونا. وأوضح تحليل هيكل الصناعة التحويلية بأبعاده المختلفة في مصر وأثر أزمة جائحة كورونا فى القسم الأول من الدراسة أن أكثر من ثلث الواردات يتكون من سلع وسيطة، وقد أدى ذلك إلى مشكلات حادة فى انتاج الصناعة مع انخفاض الواردات فى المرحلة الأولى للجائحة، وهو ما يرجح اعتبار السلع الوسيطة سلعًا استراتيجية، ويبرر استخدام منهجية تحليل المدخلات والمخرجات، والتي تركز على تحليل التشابكات القطاعية فى مجال الاستخدامات الوسيطة، وذلك مع التسليم بوجود معايير أخرى متعددة لتحديد أولويات تعميق التصنيع تم استعراضها بإيجاز فى القسم الثاني. وفي القسم الثالث تم تقدير مؤشرات الروابط الأمامية والخلفية للقطاعات المختلفة باستخدام جدول المدخلات والمخرجات لمصر فى عام 2016/2017، وتم استخدامها كمعايير للصناعات التى يجب تعميقها وهي الصناعات ذات المؤشرات الأعلى في كل من النوعين من الروابط، وذلك بالإضافة إلى معايير الأمن الصحى والغذائى والصناعات المرشحة من لجنة تعميق الصناعة. وترجح النتائج ترشيح مجموعتين متكاملتين من الصناعات؛ الأولى تتكون من الصناعات المعدنية الأساسية والصناعات الكيميائية والبتروكيماويات والصناعات الهندسية (مع التركيز على المنتجات الالكترونية) والأدوية ومواد البناء والتعدين، والمجموعة الثانية تتكون من الصناعات الغذائية والمنسوجات، والصناعات الكيميائية ،والتعدين والزراعة. وتضمن القسم الرابع نتائج الدراسة وبعض التوصيات المتعلقة بالتعامل مع مشكلات صناعة الأدوية والتعدين بشكل خاص، ومن أهمها مشكلات التسعير والقصور التشريعى، وتوصيات بسياسات وإجراءات تكميلية لعل أهمها يتمثل فى إيجاد آليات ناجعة للتنسيق بين السياسات الصناعية وبينها وبين السياسات الاقتصادية الأخرى، والتنسيق بين المؤسسات وتوسيع نطاق المشاركة فى صياغة السياسات والتعامل بجدية مع مشكلات قصور قواعد البيانات والإسراع بالتحول الرقمي فى الصناعة. الكلمات المفتاحية تعميق التصنيع- أثر جائحة كورونا- الصناعات التحويلية- المدخلات والمخرجات- الروابط الأمامية- الروابط الخلفية. The covid-19 pandemic underscored the necessity of a reasonable level of self-sufficiency in strategic goods to enhance the country’s resilience in times of crises. This study aims to specify priorities of industries to be deepened in Egypt, taking into consideration the lessons learned from covid-19 pandemic. The first section analyses the structure of manufacturing industry in Egypt and the impact of covid-19 on it. The analysis reveals that more than one third of imports are intermediate goods, which caused serious problems for manufacturing production when imports decreased in the first phase of covid-19 pandemic. This means that these goods are of strategic importance and justifies using input-output methodology, which deals with industries interdependencies mainly in intermediate consumption. Other criteria for defining priorities of industries are briefly reviewed in second section. In the third section the indicators of forward and backward linkages were computed for different sectors using the 2016/2017 input-output table for Egypt , and used as criteria for deepening industries, favoring the industries with highest indicators for both types of linkages. Other criteria were used including health and food security, in addition to the industries suggested by the committee for deepening industry. The results suggest two integrated sets of industries; the first set includes basic metals, chemical and petrochemicals industries, engineering industries (with focus on electronics), pharmaceutical industries, construction materials and mining industries. The second set includes food industries, textiles, chemical and mining industries and agriculture. The fourh section displays the main findings and some recommendations concerning the ways to deal with the challenges facing pharmaceutical and mining industries, especially pricing policies and legislation shortcomings. The study concludes with some recommendations about supplementary policies and procedures. They mainly highlight the importance of introducing effective mechanisms to ensure consistency of industrial policies and other economic policies, as well as expanding the scope of participation in formulating policies, improving inadequate data bases and accelerating digital transformation in industry